Research on Force-Saving Mechanism of Cutting Tool with Variable Curvature Directrix Rake Face Configuration - Feng Xie; Huawei Wei; Xiaofeng Chen; Chao Lei (Chinese Journal of Mechanical Engineering)
Abstract Optimizing the geometric configuration of the tool cutting surface, reducing the resistance in the cutting process and energy consumption, are always a concern. Through the method of bionic design, the directrix function of the longitudinal section of the beaver tooth rake face is extracted, and its variable curvature characteristics are analyzed. Based on this, a turning tool with variable curvature directrix configuration rake face is designed. The cutting force experiment and machining surface quality analysis experiment were carried out with the designed tool and the linear directrix configuration rake face tool respectively. The measured data of the variable curvature directrix configuration rake face tool is better than the linear directrix configuration rake face tool and its drag reduction performance of the tool is verified by experiments. Through the analysis of the working rake angle and shear angle of the tool with variable curvature directrix configuration rake face, the relationship between the parameters of the variable curvature directrix function and the working rake angle, and shear angle has been obtained. By the method of finite element simulation analysis, the stress field in the cutting zone of two different configuration tools has been analyzed. It has been found that the tool with variable curvature directrix rake face has a ‘bending moment’ effect on the tool-chip interface due to its curved surface configuration, and a ‘prying’ effect at the tool tip. These two effects promote the separation of chips from the workpiece and make the cutting process more force-saving. The research of this paper will have reference significance for the design and application of the curved surface configuration rake face tool.